In vitro efficacy of plant extracts and synthesized substances on Rhipicephalus (Boophilus) Microplus (Acari: Ixodidae) - de Souza Chagas, Ana Carolina; de Barros, Luiz Daniel [UNESP]; Cotinguiba, Fernando [UNESP]; Furlan, Maysa [UNESP]; Giglioti, Rodrigo [UNESP]; de Sena Oliveira, Marcia Cristina; Bizzo, Humberto Ribeiro (Springer, 2012)
Herbal drugs have been widely evaluated as an alternative method of parasite control, aiming to slow development of resistance and obtain low-cost biodegradable parasiticides. This study evaluated the in vitro efficacy on Rhipicephalus (Boophilus) microplus of extracts from Carapa guianensis seed oil, Cymbopogon martinii and Cymbopogon schoenanthus leaf essential oil, and Piper tuberculatum leaf crude extract and similar synthesized substances. In the immersion test, engorged females were evaluated in five dilutions ranging from 10% to 0.030625% concentration. In the larval test on impregnated filter paper, the concentration ranged from 10% to 0.02%. The treatments and controls were done in three replicates. Chemical analysis of the oils was performed by gas chromatography. The main compounds were oleic acid (46.8%) for C. guianensis and geraniol for C. martinii (81.4%), and C. schoenanthus (62.5%). The isolated and synthesized substances showed no significant effect on larvae and adult. C. martinii and P. tuberculatum showed the best efficacy on the engorged females. The LC50 and LC90 were 2.93% and 6.66% and 3.76% and 25.03%, respectively. In the larval test, the LC50 and LC90 obtained for C. martinii, P. tuberculatum, and C. schoenanthus were 0.47% and 0.63%, 0.41% and 0.79%, 0.57% and 0.96%, respectively. The fact that geraniol is present in greater quantities in C. martinii explains its higher activity in relation to C. shoenanthus. It is necessary to validate the in vivo use of safe and effective phytoparasiticidal substances. Efforts should be focused on developing formulations that enhance the efficacy in vivo and lengthen the residual period.